Why Do Migrant Children Have Poorer Mental Health Compared to Urban Children? A Network Analysis Approach - Sun J; Yao K; Zhang J; Li Y (Psychology Research and Behavior Management, 2025)
Juanjuan Sun, Kemeng Yao, Jinghui Zhang, Yan Li Shanghai Institute of Early Childhood Education, Shanghai Normal University, Shanghai, People’s Republic of ChinaCorrespondence: Yan Li, Shanghai Institute of Early Childhood Education, Shanghai Normal University, 100 Guilin Road, Xuhui District, Shanghai, People’s Republic of China, Email liyan@shnu.edu.cnIntroduction: Although mobility has been identified as a significant risk factor adversely affecting mental health and well-being, the mechanisms underlying this association remain insufficiently understood. Unlike traditional linear regression approaches, this study applies network analysis to systematically explore how multiple family risk factors collectively affect problem behaviors in migrant and urban preschoolers.Methods: A total of 1,469 children (500 urban, 959 migrant) and their parents were recruited. Network analysis examined interrelationships among family risk factors and compared risk networks between migrant and urban children. Latent profile analysis identified general and high-risk migrant groups based on problem behaviors, and network analysis explored unique risk patterns in high-risk migrant children.Results: Three key factors—household chaos, maternal punishment, and maternal executive function—proved central in shaping both internalizing and externalizing problems. Importantly, paternal influences played a more significant role within migrant families, while maternal influences were more salient in urban families. Furthermore, among migrant families, high-risk children exhibited risk networks that were densely clustered around mother- and father-centered “risk networks” independently, yet demonstrated lower overall network connectivity, suggesting a more fragmented pattern of family risk dynamics.Discussion: These findings highlight the importance of parental roles, differing social contexts, and cumulative risk in understanding child subjective well-being.Keywords: problem behaviors, networks analysis, migrant children, paternal role